Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to show that given a metric $d(x,y)$ show that $d_0(x,y) =\frac{d(x,y)}{1+d(x,y)}$ is also a metric..

It's trivial to show the first two properties, that is, $d_0\geq 0 $ & for $x=y \Longleftrightarrow$ $d(x,y) =0$ and that $d_0(x,y) = d_0(y,x)$.

However, how would I go about showing that $d_0(x,y) \leq d_0(x,z) +d_0(z,y)$. This is a bit tricky for me.

Here's what I've done so far.

$$d_0(x,y) = \frac{d(x,y)}{1+d(x,y)}\leq \frac{d(x,z)+d(z,y)}{1+d(x,z)+d(z,y)}=\frac{d(x,z)}{1+d(x,z)+d(z,y)}+\frac{d(z,y)}{1+d(x,z)+d(z,y)}$$

I'm not sure where to proceed from here.

share|improve this question
    
Well, show us what you've tried and where you're getting hung up; it will make it much easier for us to help you along. –  Nicholas R. Peterson Mar 30 at 19:52
1  
possible duplicate of math.stackexchange.com/questions/686792/… –  Sujaan Kunalan Mar 30 at 19:57

2 Answers 2

As $d(x,y), d(y,z) \geq 0$ we have that $$ 1 + d(x,y) + d(y,z) \geq 1 + d(x,y) > 0 $$So we then get that $$ \frac{d(x,y)} {1 + d(x,y) + d(y,z) } \leq \frac{d(x,y)} {1 + d(x,y)} = d_0(x,y) $$ And we then get $$d_0 (x,z) \leq \frac{d(x,y)} {1 + d(x,y) + d(y,z) } + \frac{d(y,z)} {1 + d(x,y) + d(y,z) } \leq \frac{d(x,y)} {1 + d(x,y)} + \frac{d(y,z)} {1 + d(y,z)} $$ $$= d_0(x,y) + d_0 (y,z) $$

So we have the triangle inequality, so putting what you already proved together with this, we have that $d_0$ is a metric.

share|improve this answer

Consider the function $f(t)=\frac{t}{1+t}$, this is a monotonic increasing function, since $f'(t)=\frac{1}{(t+1)^2}\ge0, \forall t\in \mathbb{R}.$

Thus for $s$ positive $f(t)\leq f(t+s)$, now apply the triangle inequality to get your desired result.

So we get $d_0(x,y)=\frac{|x-y|}{1+|x-y|}\leq \frac{|x-z|+|z-y|}{1+|x-z|+|z-y|}=\frac{|x-z|}{1+|x-z|+|z-y|}+\frac{|z-y|}{1+|x-z|+|z-y|}\leq \frac{|x-z|}{1+|x-z|}+\frac{|z-y|}{1+|z-y|}$

=$d_0(x,z)+d_0(z,y)$

Thus $d_0(x,y)\leq d_0(x,z)+d_0(z,y)$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.